Predictive models for E-commerce optimisation: effectiveness of social media and real-time interventions in online sales - Lin, Weiqiang (2019)
E-commerce platforms have become a prevalent means of selling and purchasing goods. They aim to provide efficient services for both retailers who sell goods and their customers. Optimisation of e-commerce platforms requires effective modelling of interactions among the retailers, customers and the platforms themselves. This thesis is concerned with two specific aspects for the contemporary e-commerce platform optimisation: (1) the cross-platform nature of the sales cycles that span Social Media and e-commerce platforms and require ways to assess the effects of Social Media activities on the sales and (2) the real-time involvement and session interventions to support customers' purchase decisions and provide incentives for customers to complete their purchases.